SURGICAL INTERVENTIONS IN CLAVICLE SHAFT FRACTURE: A DETAILED LOOK THROUGH THE SPECIALIZED LITERATURE - Galdino, Wellber Drayton Braga; da Cruz, Handerson Raphael Fernandes Vale; Duarte, Heitor Alves; Pinheiro, Albeysa Carla Gonçalves; de Sousa, Pedro Arthur Pinper; Santiago, Francisco Rafael Almeida; Freitas, Hannah Gislaine; Guedes, Sabrina Marques; Ferreira, Paulo Victor da Silva; Dantas, Lucca Fernandes de Araújo; Ribeiro, Joan Lucas Medeiros (Seven Editora, 2024)
Clavicle fractures are relatively common injuries, accounting for 44% of shoulder girdle fractures and 2.6% of all fractures. They occur more frequently in active young men, especially those involved in high-impact activities. For this reason, this study aims to present the main surgical interventions used in clavicle shaft fractures. This is a literature review, which was carried out between June and July 2024, which used the SciELO database, in which the term "clavicle fracture" was searched, followed by subsequent analysis of articles published in the last 5 years, 6 articles were selected. It was observed that the Blocking Plate was the main technique used in surgical interventions for clavicle shaft fractures. Despite this, there is still a great deal of debate about the optimal approach to treating these fractures. In general, the patients who underwent the surgical approach presented good results in bone consolidation and few complications after the procedure. DOI: https://doi.org/10.56238/sevened2024.037-088